ANALYSIS OF WEST NUSA TENGGARA RAINFALL TO ENSO PHENOMENON BASED ON TRMM 3B43 DATA - Amalia Nurlatifah (Lembaga Penerbangan dan Antariksa Nasional, 2019)
West Nusa Tenggara is part of the Indonesian Maritime Continent region whose weather conditions are heavily influenced by the dynamics of the Pacific Ocean and Indian Ocean. One of the dynamics that influenced the rainfall condition was the ENSO phenomenon (El Nino and La Nina). This study analyzes rainfall response in West Nusa Tenggara to ENSO phenomenon. The research data was taken from TRMM 3B43 with a monthly temporal resolution and 0.25o spatial resolution. Based on the analysis, it was found that El Nino phenomenon characterized by the heating of Sea Surface Temperature (SST) in Nino 3.4 had an impact on decreasing rainfall in NTB. In contrast, the La Nina phenomenon characterized by the cooling of SST in Nino 3.4 tends to have an impact on increasing rainfall in NTB. Nevertheless, the value of the increase and decrease of Nino 3.4 SST anomaly and rainfall in NTB itself is not linear. This is probably due to the magnitude of the ENSO phenomenon only regulating rainfall changes only, not regulating how far, how strong, or how much rainfall is reduced or increased due to the influence of the ENSO phenomenon. This is evidenced by the small correlation coefficient between Nino 3.4 SST anomaly and rainfall in NTB where the strongest value only reached -0.4 in the JJA season. In the JJA season, the correlation coefficient of Nino 3.4 SST Anomaly and rainfall in NTB tend to be negative and strongest when compared to other seasons. This is probably due to the spatial coherence of NTB rainfall in the JJA season better than the other season. Spatially, almost all areas in NTB in El Nino month experience a decrease in rainfall. In contrast, almost all areas in NTB in the month of La Nina experience an increase in rainfall. The smallest decrease or increase in rainfall during El Nino or La Nina takes place in the southwestern of Sumbawa Island. That means, the influence of the ENSO phenomenon in this region tends to be weak.